Dependence of the defect introduction rate on the dose of irradiation of p-Si by fast-pile neutrons - Dolgolenko, A.P.; Varentsov, M.D.; Gaidar, G.P.; Litovchenko, P.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
We have studied the high-resistance samples of p-Si (р00 = (3.3 ± 0.5) × × 10¹² cm⁻³ ) and n-Si (n₀ = (2.0 ± 0.3) × 10¹² cm⁻³ ) grown by the floating-zone technique after the irradiation by fast-pile neutrons at 287 К. The dose and the temperature dependences of the effective concentration of carriers have been measured. The calculation has been carried out in the framework of Gossick's corrected model. It is shown that the radiation hardness of n- and p-Si, on the one hand, is defined by clusters, and, on the other hand, by vacancy defects (acceptors) in n-Si and by interstitial defects (donors and acceptors) in p-Si. We have determined that, during the irradiation of p-Si by small doses of neutrons, the change of a charge state of interstitial defects leads to the annealing of these defects and to a decrease of their introduction rate.